191 Pulsatile Administration of Leucine Promotes mTOR Signaling and Protein Synthesis in Skeletal Muscle of Continuously Fed Preterm Pigs. (8th October 2021) - Rudar, Marko; Suryawan, Agus; Nguyen, Hanh; Stoll, Barbara; Burrin, Douglas; Fiorotto, Marta; Davis, Teresa A
Abstract: Continuous feeding does not elicit an optimal anabolic response but is required for some premature infants. We reported previously that intermittent intravenous pulses of Leu (800 μmol Leu·kg -1 ·h -1 every 4 h) to continuously fed pigs born at term enhanced skeletal muscle mTOR signaling and protein synthesis (PS). The objective of this study was to determine if the anabolic response of skeletal muscle to intermittent Leu pulses is altered following premature birth. Pigs delivered 10 d preterm by cesarean section were advanced to full oral feeding over four days (195 kcal·kg -1 ·d -1 ; 13.5 g protein·kg -1 ·d -1 ). Pigs were assigned to 1 of 4 treatments: 1) ALA (continuous feeding; 800 μmol Ala·kg -1 ·h -1 every 4 h; n = 7); 2) L1× (continuous feeding; 800 μmol Leu·kg -1 ·h -1 every 4 h; n = 6); 3) L2× (continuous feeding; 1600 μmol Leu·kg -1 ·h -1 every 4 h; n = 6); and 4) INT (intermittent feeding every 4 h; n = 5). Pigs received a Phe tracer 30 min following the amino acid pulse or intermittent feeding to measure PS in longissimus dorsi muscle. Anabolic signaling downstream of mTOR was determined by immunoblot.ResultsPS was higher in L2× and INT compared to ALA (P < 0.05) but was not different between L2× and INT; PS in L1× was intermediate and not different from other groups. Phosphorylation of 4EBP1 and S6K1 was higher in INT compared to L1× and ALA groups (P < 0.05) but was not different compared to L2×. Phosphorylation of 4EBP1, but not S6K1, was higher in L2× compared to ALA (P < 0.05); phosphorylation of 4EBP1 and S6K1 was not different between L1× and L2×.ConclusionsThese results demonstrate that intravenous Leu enhances mTOR activation and PS in LD muscle of continuously fed preterm pigs. However, the amount required may be higher than in pigs born at term.Source of Research SupportNIH and USDA.